Excessive buccal saliva in patients with Parkinson’s Disease of the French COPARK cohort - Rascol, Olivier (2020)
Fil: Rascol, Olivier. Université de Toulouse. NeuroToul COEN Center. Services de Pharmacologie Clinique et Neurosciences. Centre d’Investigation Clinique; Francia